2007
DOI: 10.3340/jkns.2007.42.5.413
|View full text |Cite
|
Sign up to set email alerts
|

Occlusion of the Middle Cerebral Artery Branch Mimicking Aneurysm

Abstract: A 26-year-old man was admitted to our department due to intermittent left hemiparesis for 3 months. Magnetic resonance image showed subacute infarction in the right precentral gyrus. Digital subtraction angiography and magnetic resonance angiography revealed an aneurysmal protrusion at the right middle cerebral artery (MCA) bifurcation. It was difficult to differentiate the aneurysm from the occlusion of the middle trunk of the MCA trifurcation. Brain single photon emission computerized tomography showed a dec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 9 publications
0
10
0
Order By: Relevance
“…In the case of a vascular stump, previous studies have suggested that clipping should not be performed. 1 , 4 In our case, the distal location of the moyamoya phenomenon relative to the occlusion site indicated compensation of the collaterals. However, the patient had symptoms of transient ischemia, which suggested that the compensation was inadequate to maintain sufficient blood flow.…”
Section: Discussionmentioning
confidence: 45%
See 2 more Smart Citations
“…In the case of a vascular stump, previous studies have suggested that clipping should not be performed. 1 , 4 In our case, the distal location of the moyamoya phenomenon relative to the occlusion site indicated compensation of the collaterals. However, the patient had symptoms of transient ischemia, which suggested that the compensation was inadequate to maintain sufficient blood flow.…”
Section: Discussionmentioning
confidence: 45%
“…Several cases of MCA vascular stump have been reported. 1 , 4 , 7 Previous studies have suggested that the MCA M2 segment may split into 2 or 3 main trunks. 8 In the case of a trifurcation, the stump of an occluded M2 segment may be easily recognized as an aneurysm located at the MCA bifurcation on the basis of the imaging findings.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hemorrhage from a dissecting aneurysm may be unrecognized or misdiagnosed as an unexplained SAH because of the difficulty in angiographic diagnosis [7 , 9] . The proximal part of the occluded MCA segment can mimic a saccular aneurysm, and it influences treatment modalities [9 , 11] .…”
Section: Discussionmentioning
confidence: 99%
“…Two authors showed that the proximal stump of the occluded MCA dissection could mimic a saccular aneurysm [9 , 11] . The shape of the proximal stump mimicking a saccular aneurysm was conical [9 , 11] . Khattar et al.…”
Section: Discussionmentioning
confidence: 99%